2020
DOI: 10.15586/jkcvhl.2020.148
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Metastatic Hereditary Leiomyomatosis and Renal Cell Cancer Syndrome-Associated Renal Cell Carcinoma Treated with a Sequence of Axitinib and Nivolumab Following Cytoreductive Nephrectomy

Abstract: Hereditary leiomyomatosis and renal cell cancer syndrome (HLRCC) associated renal cell carcinoma (RCC) is an aggressive form of type 2 papillary RCC caused by deficiency of the fumarate hydratase gene. For patients with metastatic disease, no standard treatment has been established with dismal prognosis. We report a case of metastatic HLRCC-associated RCC in a 65-year-old Japanese male whose clinical features mimicked advanced renal pelvic cancer. A durable response was achieved with a sequence of axitinib and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Iribe et al reported a case in which a patient with metastatic HLRCC underwent cytoreductive nephrectomy for diagnostic purposes, followed by treatment with nivolumab and axitinib, resulting in long-term survival. 3 Cytoreductive surgery for metastatic papillary renal cell carcinoma, which is less responsive to TKI compared to clear cell carcinoma, has demonstrated prognostic value in a retrospective study. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Iribe et al reported a case in which a patient with metastatic HLRCC underwent cytoreductive nephrectomy for diagnostic purposes, followed by treatment with nivolumab and axitinib, resulting in long-term survival. 3 Cytoreductive surgery for metastatic papillary renal cell carcinoma, which is less responsive to TKI compared to clear cell carcinoma, has demonstrated prognostic value in a retrospective study. 4 …”
Section: Discussionmentioning
confidence: 99%
“…В частности, полный ответ был получен у пациента 49 лет с метастатическим HLRCC при применении комбинации ингибитора CTLA-4 ипилимумаба с ингибитором PD-1 ниволумабом [18]. Описаны примеры эффективной комбинированной иммунотерапии пембролизумабом и таргетным препаратом акситинибом у 46-летнего пациента с HLRCC на основании результатов исследования KEYNOTE-426 и рекомендаций Управления по санитарному надзору за качеством пищевых продуктов и медикаментов США (FDA) о препаратах в 1-й линии терапии распространенного РП [19], а также достигнутого ответа на комбинированную терапию ниволумабом и акситинибом у 65-летней пациентки в аналогичном клиническом случае HLRCC [20].…”
Section: Discussionunclassified
“…Recently, the first two cases of stage IV HLRCC treated with a combination of ICPI and TKI have been published, using the combination of nivolumab-axitinib and sintilimab-axitinib, showing promising results with sustained partial responses [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%